Eating patterns & stress in Malaysian young working women - Rodriguez, Adriana Maria Ortega; Abdullah, Haslinda; Ahmad, Nobaya; Ibrahim, Rahimah (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
This paper summarizes the results obtained from a study that explored the association of stress & eating habits among Malaysian working women1. Data was collected using a questionnaire consisting of self-reported measures of health, stress symptoms, and food related behavior pattern. The results indicated significant associations between level of stress and eating habits; underlining that poor management of stress paired with unhealthy eating habits could have negative impact in young women's health and diminish their ability to cope with the demands of their competing roles in society. Thus the importance of developing health competencies that ensures positive wellbeing among emerging young working women.